Becoming Animal of Philosophy: Pragmatism, Pragrammatology, Speculative Pragmatism - Reynolds, Anthony (AM Journal of Art and Media Studies, 2021)
I argue that American pragmatism can be understood as an effort to recuperate a sense of the animality of thought and thus as an example of what Deleuze and Guattari call a “becoming animal” within the field of philosophy. At issue in this becoming animal of pragmatism is the influence of Charles Peirce’s theory of abduction on the history of pragmatism from its origins to its more recent reception within Jacques Derrida’s (pra)grammatology and Brian Massumi’s speculative pragmatism. Predicated on the evolutionary notion that animal instinct is the source of language, thought, and inquiry, Peirce’s theory of creative inference, or “abduction” as he called it, has allowed generations of pragmatists to begin “shaking philosophy’s dust off their feet and following the call of the wild” (James); to recognize in the origin of their thought something like “the movements of a wild creature toward its goal” (Dewey); to define intellectual inquiry as “doing what comes naturally” (Fish), and to pursue such inquiry “without method” (Rorty). Emerging under the ostensible heading of a new “humanism”, pragmatism exceeds what Derrida calls “the anthropological limit” from the very start, relieving humanism of its exclusive claim to logocentrism by reinscribing the question if not the origin of the logos within the animal kingdom. Yet unlike Derrida, whose rejection of biological continuism in the name of difference prevents him from committing fully to the logic of abduction, Massumi is able to rehabilitate Peirce’s theory of abduction as the foundation for his speculative pragmatism as a result of his commitment to a processual ontology that rejects binary oppositions in favor of “disjunctive syntheses” and “zones of indiscernibility.” Article received: April 15, 2020; Article accepted: July 1, 2020; Published online: April 15, 2021; Original scholarly paper